Evaluating the impact of acupuncture on perennial allergic rhinitis: A randomized placebo acupuncture control trial protocol - Chunxue Meng; Qianxi Na; Jing Zhang; Zijie Cai; Fei Wang; Qian Zhang; Shengfu Zhang; Hailong Zhao; Xuhong Tang; Ziye Chen; Qian Zhang; Bin Guo (MethodsX)
Introduction: Allergic rhinitis (AR) poses a significant global health and medical challenge. Acupuncture might serve as a therapeutic modality for allergic rhinitis, however, the empirical support for its clinical effectiveness is currently restricted.The objective of this research is to examine the therapeutic outcomes and tolerability of acupuncture treatment in the context of standard care for allergic rhinitis. Methods and analysis: A sum of 264 individuals with AR will be assigned at random to either the acupuncture (A) cohort or the placebo acupuncture (PA) cohort in an equal split of 1:1. A regimen of 12 therapeutic sessions will be conducted across a 4-week interval.The primary outcome was the 3-month post-treatment recurrence rate, assessed using the Rhinitis Control Assessment Test (RCAT) score. Additional outcomes encompass, the RQLQ, TNSS,TOSS and RMS.Participant monitoring will be conducted up to the 16th week.All participants who have been randomized will be incorporated in the analysis, with the quantitative evaluation conducted to assess the data. Ethics/dissemination: This protocol has been approved by the Research Ethical Committee of Ningxia Medical University(Permission number:Ning Medical University Ethics No.2024–3766)Trial registration number: ChiCTR2500095634.